Foundations for reading: poster book for early readers (big book) - Ancell, Claire (Folens Dunstable, 1997)
This colorful poster book introduces young children to basic words through engaging visuals. Each page features vibrant illustrations alongside simple vocabulary, making learning fun and accessible. Designed to help kids build their language skills, the book encourages interaction and exploration. Perfect for early readers, it fosters a love for words and boosts confidence in communication!